Green Marketing and Brand Image as Determinants of Sustainable Consumer Purchase Decisions: Evidence from the Coffee Retail Industry - Taj, Zarin; Chairina, Raden Roro Lia (CV. SPDFHarmony, 2026)
Background: Efficient raw material inventory management is a critical challenge for small-scale agroindustries, particularly those with limited managerial resources and fluctuating production demand. Many micro and small enterprises rely on traditional purchasing practices that often lead to overstocking, stockouts, and unnecessary holding costs. In agro-based processing industries such as milkfish floss production, ineffective inventory control can reduce operational efficiency and weaken business sustainability. The Economic Order Quantity (EOQ) model offers a systematic approach to determine optimal order quantities that minimize total inventory costs while ensuring the availability of production inputs. However, empirical applications of EOQ in small-scale agroindustry contexts remain limited. Aims: This study aims to analyze the efficiency of raw material inventory management and determine the optimal order quantity using the EOQ model in a small-scale milkfish floss agroindustry in Indonesia. Methods: This research employed a quantitative case study approach. Data were collected through direct observation, production records, and interviews with the enterprise owner. Inventory-related data, including annual demand, ordering cost, and holding cost, were analyzed using the EOQ model to determine optimal order quantity, ordering frequency, and total inventory cost. Result: The findings indicate that the existing inventory practice is less efficient compared with the EOQ-based calculation. By applying the EOQ model, the enterprise can determine a more optimal ordering quantity and reduce total inventory costs. The analysis also reveals improvements in ordering frequency and better control of raw material availability for production continuity. Conclusion: This study demonstrates that the application of the EOQ model can significantly improve raw material inventory efficiency in small-scale agroindustries. The results highlight that systematic inventory planning not only reduces operational costs but also enhances production stability and supply chain reliability. For micro and small enterprises in agro-processing sectors, adopting analytical inventory management tools such as EOQ can serve as a practical strategy to strengthen business competitiveness. Furthermore, the findings emphasize the importance of integrating basic operations management techniques into small-scale entrepreneurial practices to support sustainable agroindustrial development. Implementing structured inventory management frameworks can help small enterprises transition from intuitive decision-making toward data-driven operational strategies, ultimately contributing to improved efficiency, resilience, and long-term business sustainability.